Analysis of factors affecting the incidence of tuberculosis in Social community health center, Palembang: A cross-sectional study - Yusalin, Yusalin; Priyatno, Akhmad Dwi; Gustina, Erma (STIKes Al-Ma'arif Baturaja, 2025)
Background: Pulmonary tuberculosis (TB) is influenced by both environmental and behavioral factors. The number of pulmonary TB cases in the working area of the UPTD Palembang Social Health Centre during 2022–2024 has fluctuated and remains below the expected target. This situation indicates the need for a comprehensive analysis to identify factors influencing the occurrence and transmission of TB, considering environmental and individual characteristics. Objective: This study aimed to analyze the relationship between individual characteristics, behavioral factors, and environmental conditions with the incidence of pulmonary tuberculosis. Methods: This study employed a quantitative approach with a cross-sectional design. The population consisted of all patients visiting the DOTS Poly at UPTD Puskesmas Sosial in 2024, totaling 433 individuals. Using purposive sampling, 81 respondents were selected. Data were collected from May to June 2025 and analyzed through univariate frequency distribution, bivariate chi-square tests, and multivariate multiple logistic regression. Results: The results showed that age (p = 0.278) and education (p = 0.732) were not significantly related to pulmonary TB incidence. However, gender (p = 0.002; OR = 10.410), smoking habits (p = 0.002; OR = 11.778), ventilation (p = 0.001; OR = 51.750), and humidity (p = 0.001; OR = 14.233) were significantly associated. Among these, smoking habits were the most dominant factor influencing TB incidence. Conclusion: There is a significant relationship between gender, smoking habits, ventilation, and humidity with the incidence of pulmonary tuberculosis. Smoking habits emerged as the most dominant risk factor. Health campaigns, counseling, and education about pulmonary TB prevention should be strengthened, especially targeting high-risk groups and promoting healthy living environments.